Maternal characteristics and behavioural/emotional problems in preschoolers: how they relate to sleep rhythmic movements at sleep onset. (5th June 2018) - Laganière, Christine; Gaudreau, Hélène; Pokhvisneva, Irina; Atkinson, Leslie; Meaney, Michael; Pennestri, Marie‐Hélène
Summary: Sleep rhythmic movements have been speculated to be a form of self‐soothing. While this sleep‐related movement has been associated with lower socioeconomic status, psychopathologies and maternal characteristics, prospective studies with sizeable sample and objective measurements are lacking. The objectives were: (a) to identify maternal characteristics predicting sleep rhythmic movements in children; and (b) to document behavioural/emotional problems in preschoolers with sleep rhythmic movements. Participants were mother–child dyads ( N = 529) from the Adversity: Maternal Adversity, Vulnerability and Neurodevelopment cohort. Questionnaires evaluating socioeconomic status (prenatal), maternal depressive symptoms (prenatal, 48 months), sleep rhythmic movements (12, 18, 24, 36, 48 months), maternal anxiety trait (24 months) and children's behavioural/emotional problems (48 months) were used. Maternal sensitivity (accuracy and appropriateness of mother's responses to her baby's needs) was assessed objectively with a filmed mother–infant interaction (6 months). Generalized estimating equation was used to investigate associations between sleep rhythmic movements and maternal characteristics (depression, anxiety and sensitivity). Linear regressions were used to assess associations between sleep rhythmic movements and behavioural/emotional problems in children. Lower maternal sensitivity, higher maternal depressive symptoms and lower socioeconomic status predicted sleep rhythmic movements in children ( p < 0.05). To our knowledge, this is the first study showing that sleep rhythmic movements are associated with lower maternal sensitivity, measured objectively. This study also builds on previous reports, by documenting an association between sleep rhythmic movements and behavioural/emotional problems even in preschoolers. The presence of psychosocial factors in sleep rhythmic movements aetiology should be considered in treatment.